Volume 1: Advances in Aerospace Technology 2012
DOI: 10.1115/imece2012-86446
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Instability Modes for a Load Slung From a Helicopter

Abstract: The aerodynamic-dynamic interaction of a load slung from a helicopter in flight can lead to divergent oscillations. In this paper, interactions between degrees of freedom are explored through fundamental simulation and wind tunnel experiments of generic shapes. Video analysis of the behavior of loads in a wind tunnel provides insights into dynamic behavior, and reveals the difference in behavior of the same model between wind tunnels of different sizes. A compound pendulum motion in a plane orthogonal to a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is probably due to tunnel-wall effects. Sharma et al [57,58] studied this problem with a simple mathematical formulation using doublets to represent the forces acting on the model. They showed that spin and roll disturbances reinforced each other when the phase difference between them approached 90 degrees, and the amplification depended strongly on wall effects.…”
Section: Wind-tunnel Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably due to tunnel-wall effects. Sharma et al [57,58] studied this problem with a simple mathematical formulation using doublets to represent the forces acting on the model. They showed that spin and roll disturbances reinforced each other when the phase difference between them approached 90 degrees, and the amplification depended strongly on wall effects.…”
Section: Wind-tunnel Datamentioning
confidence: 99%
“…The reason for the difference was unambiguously traced to unsteady wall effects in the small tunnels. Sharma et al [57,58] presented a simple potential flow method to model dynamic wall effects that could amplify the roll oscillations of models suspended in a wind tunnel. Extending this work, Liberi found more modes of yaw-roll instability that would amplify, even in free air.…”
Section: Divergence Predictionmentioning
confidence: 99%
See 1 more Smart Citation